Denise Levertov in Company : Essays by Her Students, Colleagues, and Fellow Writers - Hollenberg, Donna Krolik (Book collections on Project MUSE., 2018)
"Denise Levertov (1923-1997) was an award-winning author of more than thirty books of poetry and prose featuring major themes of politics and war and, in later years, religion. Born and raised in England amid political unrest and war, Levertov moved to the United States after World War II and settled in as a passionate poet/activist for peace and environmental conservation. She initially gained recognition as a member of the Black Mountain poets and later as a highly respected mentor and educator at esteemed universities including Massachusetts Institute of Technology, Brandeis, and Stanford, where she helped shape future generations of poets. In Denise Levertov in Company, Donna Krolik Hollenberg has assembled ten essays by contemporary poets who were influenced by Levertov as either former students and/or colleagues and another ten by literary critics"--